Dampak Branchless Banking Terhadap Kinerja Keuangan PT Bank Muamalat Indonesia Tbk - Hidayati Sarah (Department of Islamic Economics, IPB University, 2015)
Branchless Banking is part of the financial inclusion program, which provides financial services performed outside bank branches using information and communication technology as well as non-bank retail agents. Branchless Banking was already done by Bank Muamalat Indonesia in cooperation with PT Pos Indonesia as an agent since 2004. This study aims to analyze the performance of Bank Muamalat Indonesia before and after Branchless Banking and formulate alternative strategies for Bank Muamalat Indonesia to improve their financial performance. This study uses the financial ratio such as Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Return on Assets (ROA), and Operating Expenses Operating Income (BOPO) with paired samples t-test method to obtain the level of significance. This study finds that the financial ratio in the form of CAR, ROA and ROA before and after Branchless Banking significantly different, while the FDR doesn’t differ significantly.